(untitled) (Journal of actual problems of jurisprudence, 2016)
In this article we study the problem of the legal institute of economic regulation of the environment and wildlife in the Republic of Kazakhstan. There are opinions of scientists about problems of legal support for economic regulation of the environment and wildlife in the Republic of Kazakhstan. Also, there are questions of separation competences of public authorities in the region of legal support for economic regulation of the environment and wildlife in the Republic of Kazakhstan. Proposes to amend the regulations on legal support for economic regulation of the environment and wildlife in the Republic of Kazakhstan. The author analyzing this concept puts forward suggestions to improve legislation in the region of legal support for economic regulation of the environment and wildlife in the Republic of Kazakhstan.